2016
DOI: 10.1073/pnas.1614946113
|View full text |Cite
|
Sign up to set email alerts
|

Planar cell polarity signaling in the uterus directs appropriate positioning of the crypt for embryo implantation

Abstract: Blastocyst implantation is a complex process requiring coordination of a dynamic sequence of embryo-uterine interactions. Blood vessels enter the uterus from the mesometrium, demarcating the uterus into mesometrial (M) and antimesometrial (AM) domains. Implantation occurs along the uterine longitudinal axis within specialized implantation chambers (crypts) that originate within the evaginations directed from the primary lumen toward the AM domain. The morphological orientation of crypts in rodent uteri was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 66 publications
0
81
0
Order By: Relevance
“…The asymmetry of implantation is encoded by a Wnt5a gradient across the uterine lumen that creates a timed evagination and subsequent implantation crypt (Cha et 2014). The regular spacing of the implantation crypts is directed by planar cell polarity signalling, as mice deficient in the non-canonical Wnt intermediary Vangl2 exhibit defective crypt formation and severely compromised pregnancy outcomes (Yuan et al 2016). Our data suggests that the asymmetry of patterning, combined with the association of bridges with vasculature, promotes co-localization of implantation with the vascular supply of the mesometrial axis, and the bridge-like structures of myometrium that provide electrical access to the entire myometrial network.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The asymmetry of implantation is encoded by a Wnt5a gradient across the uterine lumen that creates a timed evagination and subsequent implantation crypt (Cha et 2014). The regular spacing of the implantation crypts is directed by planar cell polarity signalling, as mice deficient in the non-canonical Wnt intermediary Vangl2 exhibit defective crypt formation and severely compromised pregnancy outcomes (Yuan et al 2016). Our data suggests that the asymmetry of patterning, combined with the association of bridges with vasculature, promotes co-localization of implantation with the vascular supply of the mesometrial axis, and the bridge-like structures of myometrium that provide electrical access to the entire myometrial network.…”
Section: Discussionmentioning
confidence: 71%
“…Our data suggests that the asymmetry of patterning, combined with the association of bridges with vasculature, promotes co-localization of implantation with the vascular supply of the mesometrial axis, and the bridge-like structures of myometrium that provide electrical access to the entire myometrial network. It remains unclear whether the bridge-like structures are formed postnatally concurrently with the circular and longitudinal layers (Brody & Cunha, 1989) or at the same time as the crypt structures of the lumen Cha et al 2014;Yuan et al 2016). However, as the vascular network forms before the circular and longitudinal layers (Brody & Cunha, 1989), we surmise that bridges form postnatally through the paths created by the vascular bed.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some studies showed that the loosening of cell‐cell junctions in the mouse uterine epithelium through a downregulation of E‐cadherin was a prerequisite for blastocyst attachment . Other recent investigations revealed that downstream factors of Wnt5a; that is, receptor tyrosine kinase‐like orphan receptor 1/2 (Ror1/2) and Vangl 1/2, were both essential and that the disruption of Wnt5a‐Ror‐Vangl signaling results in disorderly epithelial projections, crypt formation, and embryo spacing, and impaired implantation . Another recent study showed that Rbbj, the nuclear transducer of Notch signaling, conferred an on‐time uterine lumen shape transformation by physically interacting with uterine ERα in a Notch pathway‐independent manner .…”
Section: Molecular Mechanisms Of Embryonic Implantationmentioning
confidence: 99%
“…64,65 Other recent investigations revealed that downstream factors of Wnt5a; that is, receptor tyrosine kinase-like orphan receptor 1/2 (Ror1/2) and Vangl 1/2, were both essential and that the disruption of Wnt5a-Ror-Vangl signaling results in disorderly epithelial projections, crypt formation, and embryo spacing, and impaired implantation. 66,67 Another recent study showed that Rbbj, the nuclear transducer of Notch signaling, conferred an on-time uterine lumen shape transformation by physically interacting with uterine ERα in a Notch pathway-independent manner. 68 It is understood that the estrogendependent signaling is required for normal mammalian embryouterus interaction via growth factors, cell-cell adhesion, and cell polarity pathways.…”
Section: Estrogen-dependent Signalingmentioning
confidence: 99%